The World Book encyclopedia of people and places. (World Book, 2011)
"A 7-volume illustrated, alphabetically arranged set that presents profiles of individual nations and other political/geographical units, including an overview of history, geography, economy, people, culture, and government for each. Includes a history of the settlement of each world region based on archaeological findings; a cumulative index; and Web resources"--Provided by publisher.